PENERAPAN STRATEGI PEMBELAJARAN MODELLING THE WAY UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM (PAI) SISWA KELAS IV SD NEGERI 010 BANJAR PANJANG KECAMATAN KERUMUTAN - Euis Anegawati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The background of this study is the low learning outcomes PAI grade IV SD Negeri 010Banjar Panjang Kecamatan Kerumutan. Of the 28 students only 12 students who achieve thespecified KKM school that is equal to 65. Redahnya PAI learning outcomes is caused by: (a)instructional methods used by teachers always lectures, discussion and provision of duty; (b)teachers in presenting the material failed to give concrete examples and close to student life;(c) teachers are assigning students working on the problems that exist in textbooks used bystudents; and (d) teachers rarely express purpose of learning and less motivated students.This research is a class action, the study was conducted in two cycles by implementing alearning strategy modeling the way. Based on the results of the study, data showed that thelearning outcomes PAI increased in each cycle. This is evidenced by: (a) activity experiencedteachers peningkata on each cycle, the first cycle of meeting I obtained a score of 3 (60.00%),in the first cycle of meetings II obtained a score of 3 (60.00%), the second cycle of meetings Iobtained a score of 4 (80.00%), and the second cycle II meeting obtained a score of 5(100%); and (b) PAI learning outcomes of students also increased, in the first cycle theaverage student learning outcomes at 71, is increased in the second cycle with an average of77.3. Additionally mastery learning students also increased in the first cycle students whocompleted a total of 20 students (71.00%), in the second cycle by the number of 24 students(85.00%).